Impact of Retained Ureteral Stents on Long-Term Renal Function. Issue 2 (March 2019) - Ibilibor, Christine; Grand, Robert; Daneshfar, Cy; deRiese, Werner; Smith, Cynthia
Abstract: Introduction: The current literature does not provide any data regarding the rate of chronic kidney disease associated with retained ureteral stents. Thus, we determined the rates of major morbidities such as chronic kidney disease and severe urinary tract infection caused by retained stents. Methods: We retrospectively reviewed all records of patients at our institution who underwent ureteral stent placement and ureteral stent removal between January 2003 and October 2016. Of these patients 34 were diagnosed with a retained ureteral stent defined as a stent in place for more than 6 months. We selected 120 patients with a nonretained stent during this time frame to serve as a control group. Our primary end point was the rate of chronic kidney disease after ureteral stent removal. Results: Median duration of ureteral stent in situ was 13.7 months (range 6.4 to 146.1) in the retained group vs 32 days (range 2 days to 5.1 months) in the control group. Of the retained group 9 patients (26.47%) with normal renal function before stent placement were diagnosed with chronic kidney disease after stent removal vs 4 (3.33%) in the control group (OR 8.64, 95% CI 2.05-41.9, p = 0.0009). Conclusions: Patient counseling and measures to ensure compliance with followup are of paramount importance after stent placement as patients with a retained ureteral stent are at risk for chronic kidney disease despite removal of the retained stent.